PERANCANGAN JEMBATAN AIR MERANJAT – BATAS KOTA KAYU AGUNG KABUPATEN OGAN ILIR SUMATERA SELATAN - Putri, Andira; Rayhan Alfaridzi, Muh; Muchtar, Zainuddin; Hassasi, Bastoni (PILAR, 2025)
The Air Meranjat Bridge - Batas Kota Kayu Agung, Ogan Ilir Regency, South Sumatera connects the Indralaya - Kayu Agung cross Sumatra road. The design of the Air Meranjat bridge includes the upper structure and lower structure using the Practical Guide to Bridge Technical Planning method 2021. From the design results obtained the dimensions of the prestressed girder 1.7 m x 0.7 m and a length of 40.6 m, Pillars with dimensions of 3.929 m x 4 m and a length of 11 m, Abutment with dimensions of 6.35 m x 5 m and a length of 10.6 m, Piles used diameter 0.5 m 24 m depth. The cost for the construction of the Air Meranjat Bridge is Rp.10.555.155.490,000 with an implementation time of 202 days.